2005
DOI: 10.1007/s00216-005-0160-0
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a chromium-reactor design for measuring δ2H values of solid polyhalogenated compounds using direct elemental analysis and stable isotope ratio mass spectrometry

Abstract: 2H/1H isotope ratios of polyhalogenated compounds were determined by elemental analysis and isotope ratio mass spectrometry (EA-IRMS). Initial measurements with standard EA-IRMS equipment, which used high-temperature pyrolysis to convert the organic compounds into hydrogen, did not achieve significant signals for polychlorinated pesticides and related compounds, presumably due to the formation of HCl instead of hydrogen. To reverse this problematic reaction, a chromium reactor was incorporated into the element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…Replicated sample preparation and measurement of a blank urine showed comparable results after correction was applied (Table 3). Unfortunately, fluorine was found to be an inadequate derivatisation agent, with HF emerging from the ion source after short time despite the use of copper wires for removal of HF from the gas stream, destroying the ceramic thermal conversion tube and causing additional memory effects by the formation of HF during combustion [28,99]. Despite addition of hydrogen to the analyte, acetylation was found to be a reasonable derivatisation process.…”
Section: First Results On Endogenous Hirmentioning
confidence: 99%
“…Replicated sample preparation and measurement of a blank urine showed comparable results after correction was applied (Table 3). Unfortunately, fluorine was found to be an inadequate derivatisation agent, with HF emerging from the ion source after short time despite the use of copper wires for removal of HF from the gas stream, destroying the ceramic thermal conversion tube and causing additional memory effects by the formation of HF during combustion [28,99]. Despite addition of hydrogen to the analyte, acetylation was found to be a reasonable derivatisation process.…”
Section: First Results On Endogenous Hirmentioning
confidence: 99%
“…found that HTC methods using glassy carbon produce hydrogen cyanide (HCN) for nitrogenous organics. This causes a problem when normalizing the results of δ 2 H values of nitrogenous organic samples to calibration standards, such as water, that contain no nitrogen., An alternative method using elemental chromium instead of glassy carbon was described by Armbruster et al ., and was later modified by Gehre et al . Here, we tested both reactor type systems.…”
Section: Methodsmentioning
confidence: 99%
“…The method was proposed by M. Gehre during a recent IAEA consultants meeting on hydrogen reference materials and results will be published separately . It is similar to the system described by Armbruster et al . for δ 2 H measurement of solid polyhalogenated compounds.…”
Section: Methodsmentioning
confidence: 99%
“…As an alternative to the HTC technique, chromium has been used in lieu of glassy carbon, albeit at lower reaction temperatures, usually around 1000 to 1100 °C . These systems have been applied mostly to water and for reducing gaseous compounds.…”
mentioning
confidence: 99%